In Vitro Anti-Glioblastoma Activity of Echinocereus engelmannii- and Echinocereus pectinatus-Associated Bacterial Endophyte Extracts - Ana L. Delgado-Miranda; Ricardo Gomez-Flores; Nancy E. Rodríguez-Garza; Orquídea Pérez-González; Patricia Tamez-Guerra; Diana Caballero-Hernández; Diana L. Clark-Pérez; Ramiro Quintanilla-Licea; Andrés García; César I. Romo-Sáenz (Life)
Glioblastoma is the most common and aggressive brain tumor in adults. However, due to the limitations of conventional treatments, as well as their side effects, there is a need to develop more effective and less harmful therapy strategies. There is evidence that plants endemic to northern Mexico possess biological activities that positively impact human health, particularly against cancer. Echinocereus engelmannii and Echinocereus pectinatus are cacti from the north of Mexico that produce bioactive compounds with antitumor activity. We obtained methanol extracts from previously isolated and fermented microorganisms associated with these cacti. Cell lines of extracts with cytotoxicity against glioblastoma cells U87, neuroblastoma cells SH-S5Y5, and Schwann neuronal cells (healthy control) were evaluated, using a colorimetric 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazole bromide (MTT) reduction technique. The selective cytotoxicity extracts were analyzed using liquid chromatography tandem mass spectrometry (LC/MS2). We isolated 19 endophytic and soil-associated microorganisms from both cacti. Two of them were selected for their high percentages of tumor growth inhibition. The microorganism ES4 possessed the best activity with an IC50 of 17.31 ± 1.70 µg/mL and a selectivity index of 3.11. We identified the bacterium Stenotrophomonas maltophilia by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) from the most active microorganisms against tumor growth. LC/MS2 characterized the HS4 extract, and the most abundant group (50.0%) identified included carboxylic acids and derivatives, particularly bisgerayafolin A, Cyclo (Pro-Leu), maculosin, and tryptophan. In conclusion S. maltophilia extract inhibit the growth of glioma cells, showing greater sensitivity in the U87 cell line.